Pelatihan Kepemimpinan dan Manajemen Organisasi Siswa SMK Empat Lima Surakarta - Sri Partini; Agus Setyo Utomo; Tri Wuryanto; M Ali Mursidi; Muhammad Luthfi Hamdani; Chan Uswatun Khasanah (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
To become a leader, a person must study and train themselves to have the character, abilities or qualities that a leader should have. Students in general are also administrators of intra-school organizations (OSIS) who are one of the seeds of future leaders and have an obligation to drive behavioral changes in their respective schools so that they become better. As a form of concern in building a leadership model that has integrity, Akbara Surakarta Polytechnic conducts leadership training and coaching for OSIS administrators and students at SMK Empat Lima. The methods used in this training are lecture activities, question and answer sessions, case study discussions, by explaining the basic concepts of visionary leadership, participatory leadership styles, leadership in organizational change and how to make decisions correctly, prepare accountability reports for activities. After this training, it is hoped that OSIS administrators and students will have and demonstrate leadership behavior skills that are ready to face challenges and can inspire students in their respective school and community environments.